PROBLEMS AND SOLUTIONS IN TEACHING ENGLISH (A CASE AT SMP NEGERI 1 BAUBAU) - Risa Melati; Wa Ode Hanafiah; La Dunifa (English Education Department, 2022)
The problem statements of this research were: (1) what kind of teachers’problems in teaching English at seventh grade of SMP Negeri 1 Baubau; and (2) how do teachers overcome the problems in teaching English at seventh grade of SMP Negeri 1 Baubau. The purpose of the research were: (1) to reveal the kind of teachers problems in teaching English at seventh grade of SMP Negeri 1 Baubau; and (2) to find out the solutions the teachers overcome the problems in teaching English at seventh grade of SMP Negeri 1 Baubau. This research was a qualitative research by applying a qualitative description method. The subjects of this research were ten students of the seventh grade and a teacher of SMP Negeri 1 Baubau. The instruments used were observation, interview, and document study. The technique of data analysis used were data collection, data reduction, data presentation (display data), and conclusion. Based on findings in this research, the result showed that the seventh grade English teacher faced problems when teaching English, they are lack of motivation, lack of vocabulary, lack of time allocation and lack of facility. Based on the problems, teachers took solutions to overcome these problems by creating a pleasant atmosphere, being fun teacher, using song, drama, vocabulary game and code switching, simplifying materials, increasing time allocation, as well as providing facilities in school.